GEOLOGY AND STATIC 3D RESERVOIR MODELLING OF âBATANGHARIâ FIELD, AIR BENAKAT FORMATION, JAMBI SUB BASIN, SOUTH SUMATRA BASIN - Adi Prabowo, Rizal
The “Batanghari” field is administratively located 41 km to the west of Jambi City, Jambi Province which is included in the UTM 48 S zone with coordinates 313696,7 – 312901,7 easting and 9798830,4 – 9803639,3 northing. Located in Jambi Sub-Basin, South Sumatra Basin with an area of 11.25 km2 and included in the development stage field. The study is conducted at 3 research intervals in the Air Benakat Formation, “Batanghari” Field with total of 141 wells. The study aims to [1] determine the geological condition including geological structure, facies association, and the depositional environment of the research intervals, [2] to find out the distribution of reservoir property as well as facies association and petrophysical data at the research intervals and [3] estimate the amount of hydrocarbon reserves (STOIIP) at the research intervals. The method used consists of stratigraphic analysis, petrophysical analysis, analysis of the geological structure of the study area, 3D static reservoir modelling, and estimation of hydrocarbon reserves (STOIIP) of the research intervals. Description of cores and their groupings yield 9 lithofasies (Sb, Sbf, Spic, Sba, Msl, Sgba, Sxl, Sfl) with facies associations in the form of Distributary Mouth Bar which is potential to be a reservoir zone and Interdistributary Bay as not interested zone. The research interval deposition environment is a delta front environment dominated by rivers that are influenced by sea tides with Northeast – Southwest trending of sedimentation. Based on petrophysical analysis, the cuts-off value for Vshale reservoir property is 0.61; Effective Porosity (PHIE) is 0.1; and Water Saturation (Sw) is 0.7. These cut-off values are used for making NTG calculation. Analysis of the geological structure of the study area shows that there are 3 main structures namely Anticline with relatively Northwest-Southeast oriented, Normal Fault with relatively Northeast - Southwest oriented (Jambi Pattern), and Reverse Fault with relatively Northwest - Southeast oriented (Lematang and Sumatra Patterns). Static 3D reservoir modelling includes structure, facies, and petrophysical properties modeling performed to determine reservoir geometry, property distribution, and estimation of hydrocarbon reserves. Facies and petrophysical modeling use co-krigging from the probability trend of facies association. This probability trend is quality controlled by the facies association pie map which is results from the stratigraphic sequence correlation, thus giving high level of confidence to the probability trend of facies associations. Based on the calculation process, the estimation of hydrocarbon reserves (STOIIP) in the reservoir zone 1 is 45 MMbbl, not interested zone is 0 MMbbl, and reservoir zone 2 is 24 MMbbl, which makes a total of 69 MMbbl of STOIIP in the research interval.